Environmental Theology and Its Relevance to Islamic Law: Perception of Makassar Muslim Scholars, Indonesia - Latif, Muhaemin; Hanafi, Darmawati; Damis, Rahmi; Goncing, Abdi (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
This article discusses environmental theology with Islamic law from the perspective of scholars and scholars in Makassar City, South Sulawesi. The research uses qualitative methods with a theological approach and Islamic law as an analytical tool. Theology is used to analyze Islamic concepts of the environment as opposed to Islamic law. In obtaining the data, researchers interviewed religious figures who became role models for the people of Makassar, in addition to using literature study techniques. The results showed that Makassarese Muslim scholars are well aware that environmental theology is an alternative solution to overcome the environmental crisis. They believe that the two main sources of Islam, the Quran and Hadith, pay great attention to the protection and maintenance of the environment. Similarly, Prophet Muhammad PBUH is the best example among leaders who care deeply about the environment. Furthermore, this study also concludes that first, environmental theology is a theology that not only discusses man's relationship with God but also discusses man's relationship with social, cultural, environmental, and social reality. Environmental theology focuses on the extent of human concern for nature and the environment. Second, the foundation of environmental theology can be traced from two main sources of Islam, namely the Qur'an, and Hadith. The Qur'an pays great attention to the protection and preservation of the environment. Likewise, Prophet Muhammad PBUH, in his various traditions also emphasized the importance of protecting and maintaining the environment. Third, environmental theology is closely related to Islamic law specifically ecological fiqh, which focuses on practical explanations of how to protect the environment. If environmental theology is oriented towards philosophical foundations in environmental conservation, then Islamic law requires the importance of protecting the environment as a benefit for humans and nature.